Interplay between Heart Disease and Metabolic Steatosis: A Contemporary Perspective - Ramadan, Mohammad Said (J Clin Med, 2021)
The liver-heart axis is a growing field of interest owing to rising evidence of complex bidirectional interplay between the two organs. Recent data suggest non-alcoholic fatty liver disease (NAFLD) has a significant, independent association with a wide spectrum of structural and functional cardiac diseases, and seems to worsen cardiovascular disease (CVD) prognosis. Conversely, the effect of cardiac disease on NAFLD is not well studied and data are mostly limited to cardiogenic liver disease. We believe it is important to further investigate the heart-liver relationship because of the tremendous global health and economic burden the two diseases pose, and the impact of such investigations on clinical decision making and management guidelines for both diseases. In this review, we summarize the current knowledge on NAFLD diagnosis, its systemic manifestations, and associations with CVD. More specifically, we review the pathophysiological mechanisms that govern the interplay between NAFLD and CVD and evaluate the relationship between different CVD treatments and NAFLD progression.